Observation of fission events in the 14N+181Ta system at projectile energies ≈ 5-6 MeV/A. (August 2019) - Sharma, Vijay R; Kumar, R; Singh, B P; Aguilera, E F; Shuaib, Mohd; Mukherjee, S; Dubey, R; Singh, P P; Kumar, S; Appannababu, S; Yadav, Abhishek; Sharma, M K; et al.
Abstract: Present paper reports the mass distribution of fission events in the 14 N+ 181 Ta reaction at four different projectile energies viz., 82.2 ± 0.8, 79.18 ± 0.82, 76.8 ± 1.2 and 72.9 ± 0.91 MeV using recoil catcher technique followed by off-line γ-ray spectrometry. A single peaked broad Gaussian mass curve has confirmed the nonappearance of any non-compound nuclear fission. Further, the variance of the mass distribution is compared with the existing literature data. It has been observed that the lower mass asymmetric system results in a lower variance of the mass distribution.